Enolisation Kinetics of m-Nitro Acetophenone - Swati Malhotra Swati Malhotra; Dipika Jaspal (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
m-Nitroacetophenone was chosen for the study of kinetics of enolisation. The rate of the reaction was studied by iodination. The kinetics of the reaction was monitored under several conditions of variation of ketone concentration, dielectric constant of the medium , temperature, effect of catalyst etc. In addition to this four different amino acids viz. β-alanin, DL-alanin, L-alanin and Glycine were tested as catalyst for the enolisation process. The rate of enolisation was found to increase with the increase in then ketone concentration , percentage composition of the solvent mixture and also with the increase in the dipole moments of the amino acids. Pseudofirst order rate kinetics was operational and the rate constants were found to increase with the increase in the amino acid molarity. Linear plots obtained for log of rate constants versus reciprocal of temperature which were in good agreement with Arrhenius equation. The values of thermodynamic parameters like Entropy (∆S≠) , Enthalpy (∆H≠), energy of activation (∆Ea) and Free energy(∆F≠) were calculated and were found to be 2.6186 e.u. , 20.85 e.u. ,23.46 k cal mol-1 and 20.0 k cal mol-1 respectively. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)